Photoshop CS6 - Wooldridge, Mike (Teach yourself visually., 2012)
Step-by-step screen shots show you how to tackle more than 160 Photoshop CS6 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Photoshop CS6 in no time--